Effect of Systolic Cardiac Function on Passive Leg Raising for Predicting Fluid Responsiveness: A Prospective Observational Study - Xiang Si; Dai-Yin Cao; Juan Chen; Jian-Feng Wu; Zi-Meng Liu; Hai-Lin Xu; Min-Ying Chen; Yong-Jun Liu; Xiang-Dong Guan (Chinese Medical Journal, 2018)
Background: Passive leg raising (PLR) represents a “self-volume expansion (VE)” that could predict fluid responsiveness, but the influence of systolic cardiac function on PLR has seldom been reported. This study aimed to investigate whether systolic cardiac function, estimated by the global ejection fraction (GEF) from transpulmonary-thermodilution, could influence the diagnostic value of PLR. Methods: This prospective, observational study was carried out in the surgical Intensive Care Unit of the First Affiliated Hospital of Sun Yat-sen University from December 2013 to July 2015. Seventy-eight mechanically ventilated patients considered for VE were prospectively included and divided into a low-GEF (<20%) and a near-normal-GEF (≥20%) group. Within each group, baseline hemodynamics, after PLR and after VE (250 ml 5% albumin over 30 min), were recorded. PLR-induced hemodynamic changes (PLR-Δ) were calculated. Fluid responders were defined by a 15% increase of stroke volume (SV) after VE. Results: Twenty-five out of 38 patients were responders in the GEF <20% group, compared to 26 out of 40 patients in the GEF ≥20% group. The thresholds of PLR-ΔSV and PLR-Δ cardiac output (PLR-ΔCO) for predicting fluid responsiveness were higher in the GEF ≥20% group than in the GEF <20% group (ΔSV: 12% vs. 8%; ΔCO: 7% vs. 6%), with increased sensitivity (ΔSV: 92% vs. 92%; ΔCO: 81% vs. 80%) and specificity (ΔSV: 86% vs. 70%; ΔCO: 86% vs. 77%), respectively. PLR-Δ heart rate could predict fluid responsiveness in the GEF ≥20% group with a threshold value of −5% (sensitivity 65%, specificity 93%) but could not in the GEF <20% group. The pressure index changes were poor predictors. Conclusions: In the critically ill patients on mechanical ventilation, the diagnostic value of PLR for predicting fluid responsiveness depends on cardiac systolic function. Thus, cardiac systolic function must be considered when using PLR. Trial Registration: Chinese Clinical Trial Register, ChiCTR-OCH-13004027; http://www.chictr.org.cn/showproj.aspx?proj=5540.